2004
DOI: 10.5486/pmd.2004.3312
|View full text |Cite
|
Sign up to set email alerts
|

Power values of polynomials and binomial Thue--Mahler equations

Abstract: Let p 1 , . . . , p s be distinct primes, and S the set of integers not divisible by primes different from p 1 , . . . , p s . We give effectively computable upper bounds for n in the equations (1) f (x) = wy n , (5) F (x, z) = wy n and (9) ax n − by n = c, where f ∈ Z[X] is a monic polynomial, F ∈ Z[X, Z] a monic binary form, the discriminants D(f ), D(F ) are contained in S, and x, y, z, w, a, b, c, n are unknown non-zero integers with z, w, a, b, c ∈ S, y / ∈ S and n ≥ 3. It is a novelty in our paper that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…with some nonzero integer w. Now, since n ≥ 17 by (i), one can apply Lemma 11 to equation (12) which implies that n | h + n . But as is remarked after Lemma 11, it then follows that n > 12 • 10 6 which is a contradiction.…”
Section: Auxiliary Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…with some nonzero integer w. Now, since n ≥ 17 by (i), one can apply Lemma 11 to equation (12) which implies that n | h + n . But as is remarked after Lemma 11, it then follows that n > 12 • 10 6 which is a contradiction.…”
Section: Auxiliary Resultsmentioning
confidence: 99%
“…(28, 43, 19) (39, 44, 13) (5,22,31) (10,37,11) (17,46,17) (23,29,13) (29, 33, 17) (39, 44, 17) (5,27,11) (11,32,19) (18,29,17) (23,29,19) (29, 37, 19) (39, 46, 17) (5,39,13) (11,34,11) (18,41,13) (23,34,13) (29, 41, 11) (39, 50, 13) (5,42,11) (12,23,13) (18,47,17) (23,35,13)…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that a wide range of diophantine problems leads to such equations (see e.g. [1], [2], [3], [12], [13], [15], [17], [19], [18]).…”
Section: Proof Of the Theoremmentioning
confidence: 99%
“…Moreover, in the case when n is also unknown, Tijdeman [26] showed that max{|x|, |y|, n} is still effectively bounded for every integer solution (x, y, n) with |xy| > 1 and n ≥ 3. This effective finiteness result has been extended in [11] to the more general situation when, for a finite set of primes S, the numbers A, B, C are unknown S-units rather than fixed, that is all prime factors of A, B and C lie in S.…”
Section: Introductionmentioning
confidence: 99%